Uncovering molecular mechanisms of soybean response to 12C6+ heavy ion irradiation through integrated transcriptomic and metabolomic profiling - Honglei Ren; Bixian Zhang; Chunlei Zhang; Xiulin Liu; Xueyang Wang; Fengyi Zhang; Kezhen Zhao; Rongqiang Yuan; Ahmed M. Abdelghany; Sobhi F. Lamlom (Ecotoxicology and Environmental Safety)
Ion beam mutagenesis is an advanced technique capable of inducing substantial changes in plants, resulting in noticeable alterations in their growth. However, the precise molecular mechanisms underlying the effects of radiation on soybeans remain unclear. This study investigates the impact of ionizing radiation on soybean development through a comprehensive approach that integrates transcriptomics and metabolomics. A total of 1500 rounds of disease-free soybean seeds underwent irradiation with 270 MeV/u 12C6+ ion beams, administered at doses of 0, 120, and 150 Gy. Our results revealed that key growth-related parameters, including plant height, branch number, number of pods per plant, and number of seeds per plant, were closely monitored and exhibited significant declines with increasing radiation doses. Transcriptomic analysis identified a multitude of differentially expressed genes (DEGs), with 6013, 3588, and 340 genes significantly altered in high vs. control, low vs. control, and high vs. low-dose irradiation comparisons, respectively, while metabolomic profiling unveiled 445, 445, and 218 differentially expressed metabolites (DEMs) in analogous comparisons. This comprehensive analysis ultimately pinpointed 123 key metabolites influenced by radiation stress. Putting together transcriptomic and metabolomic data showed strong connections between genes and metabolites, which had a big effect on pathways like pyruvate metabolism, ABC transporters, and glutathione metabolism. This underscores the comprehensive reprogramming of soybean metabolism to address irradiation-induced challenges. Specifically, we observed significant up-regulation of 24 DEGs, notable down-regulation of 8 DEMs, and significant activation of 15 metabolic pathways, all of which contributed to the observed phenotypic changes. These findings elucidate soybeans' complex molecular reactions to ionizing radiation, helping us understand how radiation-induced genetic and metabolic alterations affect plant growth.